A Review on Hepatoprotective and Immunomodulatory Herbal Plants - Ilyas, Uorakkottil; Katare, Deepshikha P.; Aeri, Vidhu; Naseef, Punnooth Poonguzi (Pharmacognosy Reviews)
The liver is the most important organ that plays an important role in maintaining various physiological processes in the body. Hepatitis is an inflammation of the liver and is characterized by the presence of inflammatory cells in the tissue of the organ. There are five main viruses, referred to as types A, B, C, D, and E. These five types are of the greatest concern because of the burden of illness and death. Liver injury or liver dysfunction is a major health problem that challenges not only health care professionals but also the drug regulatory agencies and the pharmaceutical industry. Herbal medicines have been used in the treatment of liver disease for a long time. The immune system is the part of body that diagnoses the pathogen by using a specific receptor to reveal immediate response by the activation of immune components cells, chemokines, and cytokines, and also the release of the inflammatory mediator. They potentiate and modulate the immune system. The plant-derived phytoconstituents (polysaccharides, proteins and flavanoids, lignans, rotenoids, etc.) stimulate the immune system and maintained hepatic diseases. There are a number of hepatoprotective and immunomodulatory herbs that have been reported. The present review is aimed at compiling data on promising phytochemicals from hepatoprotective and immunomodulatory herbs.
Keywords: Hepatoprotective herb; immunomodulatory herb; nitric oxide